2020
DOI: 10.1186/s40981-020-00351-6
|View full text |Cite
|
Sign up to set email alerts
|

Difficult airway management of a patient with limited range of motion in the temporomandibular joint and cervical extension caused by psoriatic arthritis: a case report

Abstract: Background: Psoriasis vulgaris, a chronic inflammatory skin disease, rarely causes temporomandibular arthritis. We report a case of difficult airway management of a patient with limited range of motion in the temporomandibular joint and cervical extension caused by psoriatic arthritis. Case presentation: A 33-year-old man was scheduled to undergo laparoscopic colectomy. On admission, he was diagnosed with psoriatic arthritis. After induction of general anesthesia, we attempted intubation using Pentax Airway Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Among clinical findings, nine cases had limited mouth opening and seven had TMJ pain. The psoriasis manifestations were skin pigmentation, 14 plaque psoriasis on the scalp 15,19,20 on elbows, 21 rash on various parts of the skin, 22 dry mouth and eyes 23 or psoriasis vulgaris on different parts of the skin 24 . Seven cases reported involvement of other joints as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among clinical findings, nine cases had limited mouth opening and seven had TMJ pain. The psoriasis manifestations were skin pigmentation, 14 plaque psoriasis on the scalp 15,19,20 on elbows, 21 rash on various parts of the skin, 22 dry mouth and eyes 23 or psoriasis vulgaris on different parts of the skin 24 . Seven cases reported involvement of other joints as well.…”
Section: Resultsmentioning
confidence: 99%
“…The psoriasis manifestations were skin pigmentation, 14 plaque psoriasis on the scalp 15,19,20 on elbows, 21 rash on various parts of the skin, 22 dry mouth and eyes 23 or psoriasis vulgaris on different parts of the skin. 24 Seven cases reported involvement of other joints as well. Blood tests revealed an elevated C-reactive protein level in two cases, 14,24 and a normal level in one case.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, we tried to use the McGrath video laryngoscope with the fiberoptic intubation on standby. Several case reports demonstrated that fiberoptic bronchoscope-assisted intubation is a useful procedure both as a primary and as a rescue option for definitive airway management in various difficult airway cases (Hariharasudhan et al, 2016;Lim & Wong, 2019;Maeda et al, 2020;Pang et al, 2015;Sung et al, 2014). Sung et al reported a case of successful fiberoptic nasotracheal intubation in temporomandibular ankylosis with minimal mouth opening (Sung et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of anesthesiologists focus on the TMJ function evaluation as it relates to optimal intubating conditions [ 7 ]. Difficulties with intubation are especially common in patients with limited mouth opening such as those with TMJ ankyloses [ 8 , 9 , 10 , 11 ]. However, proper TMJ assessment is required both before and after anesthesia in order to avoid or minimize temporomandibular complications [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%